Analysis and Forecast Based on the Kinetic Equation for Changing the Numerical Composition of Living Systems - Alexandrovich Victorov Alexander; Alexandrovich Kholodnov Viacheslav (Journal of Biotechnology and Biomedical Science, 2020)
The possibility of applying the kinetic theory of aging of biological species published earlier by the authors of this work to assess and predict changes in the number of specific populations is evaluated. The populations of the USA, China and Russia, as well as the population of mice observed in the experiment
Keywords: Model